Insights and perceptions: Investigating pregnant women's attitudes, understanding, and factors influencing knowledge regarding medication usage during pregnancy-A cross-sectional study. - Abdullah R Al-Khawlani; Qutaiba A Qasim; Abdulsalam M Halboup; Samar Thiab; Mohammed Zawiah; Fahmi Y Al-Ashwal (PLoS ONE)
Background Medication use during pregnancy is a critical concern due to potential risks to both the mother and fetus. To the extent of our knowledge, there has been no prior research to assess medication use and identify the specific factors of pregnant women within the Yemeni community. This study aimed to investigate the knowledge, beliefs, and practices of Yemeni pregnant women regarding medication use and assess the factors associated with the knowledge during pregnancy. Methods A cross-sectional multi-center study was conducted through face-to-face interviews using a validated structured questionnaire. The study was conducted on pregnant women receiving antenatal care at tertiary care hospitals in four governorates in Yemen. Univariable and multivariate logistic regressions were employed to examine the relationship between participant variables and their knowledge. A P-value of less than .05 was considered statistically significant. Results Out of the 1003 pregnant women, 35.4% (n = 355) were aged 21-25 years, 33.9% (n = 340) had primary education, 73.6% (n = 738) lived in urban areas, 12.2% (n = 122) were smokers, 38.3% (n = 384) reported chewing khat, and the majority (90.2%, n = 905) were unemployed. Also, 65.5% (n = 657) of the participants reported taking folic acid in their current pregnancy. A total of 2,623 medications were utilized during pregnancy, with 17.8% during the first trimester (n = 468). Around 39.3% (n = 1,037) of medications used fell under the blood and blood-forming organs category. Education level (AOR: 4.00, P < .001), insurance status (AOR: 1.71, P = .026), information about medication risks to the fetus (AOR: 1.96, P = .023), the use of folic acid either in a previous pregnancy (AOR: 1.65, P < .008) or in the current pregnancy (AOR: 4.26, P < .001), and checking the medication leaflet (AOR: 5.67, P < .001) were predictors of higher knowledge. Conclusion The findings underscore the pressing need for educational interventions aimed at pregnant women. By bridging knowledge gaps and promoting informed decision-making, such initiatives can contribute to a safer and healthier pregnancy journey, reducing the inclination towards self-medication.